Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1002/jor.25518
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a machine learning technique for segmentation and pose estimation in single plane fluoroscopy

Abstract: Kinematics of total knee replacements (TKR) play an important role in assessing the success of a procedure and would be a valuable addition to clinical practice; however, measuring TKR kinematics is time consuming and labour intensive. Recently, an automatic single-plane fluoroscopic method utilizing machine learning has been developed to facilitate a quick and simple process for measuring TKR kinematics. This study aimed to validate the new automatic single-plane technique using biplanar radiostereometric ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…However, errors for components not used in the development were comparable to errors of components used in the development. 23,28 Accordingly, it can be concluded that the magnitude of errors herein are representative of errors for arbitrary components.…”
Section: Discussionmentioning
confidence: 86%
“…However, errors for components not used in the development were comparable to errors of components used in the development. 23,28 Accordingly, it can be concluded that the magnitude of errors herein are representative of errors for arbitrary components.…”
Section: Discussionmentioning
confidence: 86%